High-dose immunosuppressive therapy with autologous hematopoietic stem cell transplantation in multiple sclerosis: a modern view of the method (review of literature) - A. Yu. Polushin; Yu. R. Zalyalov; N. A. Totolyan; A. D. Kulagin; A. A. Skoromets (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова)
There is an increase in the incidence of multiple sclerosis in the world. Only in half of the cases, standard therapy allows for a short time to achieve control over this disease. High-dose immunosuppressive therapy and autologous hematopoietic stem cells transplantation is a promising and effective method of treating autoimmune diseases, including multiple sclerovsis. Over the past 20 years, progress has been made in understanding the immune mechanisms of the method. At present, the frequency and severity of adverse events of therapy significantly decreased by reducing the intensity of conditioning regimens. The objective of this review was to analyze scientific publications on the effectiveness of the method, and the data on the optimal conditions and criteria for its use in multiple sclerosis.